Comparison of Survival Rates of Syrian Refugee Versus Turkish Pediatric Patients with Leukemia - Cengiz Bayram; Tuba Nur Tahtakesen; Özlem Terzi; Ali Ayçiçek; Şadan Hacısalihoğlu; Hüseyin Avni Solgun; Esra Esra Arslantaş; Gül Nihal Özdemir; Sibel Tekgündüz (Baiman Bauntung Batuah Center, 2023)
Although survival rates are increasing in acute leukaemias today, this rate is lower in developing countries; there are very few studies conducted on this matter in refugee patients. This research aims to evaluate the survival rate in pediatric Syrian refugee patients with acute leukaemia and compare it with Turkish pediatric leukaemia patients. A total of 144 patients diagnosed with acute leukaemia were included in the study, and their files were reviewed retrospectively. Nineteen 144 patients (13%) were Syrian refugees, and 125 (87%) were Turkish patients. The median age of the Syrian refugees and Turkish patients was 6.9 years (range 1-18 years) and 7.2 years (range 2-18 years), respectively, and gender distribution was similar for both groups (p:0.32). The relapse rate and rate of patients in the high-risk leukaemia group were higher in the Syrian refugee patient group (p=0.05). The survival rates of the Syrian refugee patients at the 11th month and 23nd month of the follow-up were 87.5% and 70%, respectively. The survival rates of the Turkish patients in the 23rd month and 44th month of the follow-up were 96.6% and 85%, respectively. The survival rates of the Turkish patients were significantly higher (p<0,001). The odds ratio of mortality adjusted for being a Syrian refugee was 5.3 (with a 95% confidence interval, 1.5 to 18.3). No difference was observed between the groups regarding compliance with treatment. Survival rates of the Syrian refugee leukaemia patients were lower, and the rate of patients in the high-risk leukaemia group and the relapse rate was higher in Syrian refugee patients compared to Turkish patients.